Fostering Creative Thinking Skills on High and Low Cognitive Levels Students with Project-based Inquiry Learning - Vonny; Diana Vivanti Sigit; Supriyatin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Integrating the development of soft skills, such as creative thinking, into classroom learning is essential. This study aims to analyze whether students' creative thinking skills can be enhanced through project-based inquiry learning that is varied for high and low cognitive levels. This research used a quasi-experimental design of 2x2 factorial. The research was done at a private senior high school for over a month. Forty-six eleventh-grade students were involved in this study. The samples consist of 23 high- and 23 low-cognitive ability students, which were determined using a cognitive ability instrument. The creative thinking skill was assessed by comparing the N-gain of the pretest and posttest scores using a creative thinking instrument. The results revealed that the cognitive level affects creative thinking skills significantly, and there is an interaction effect between the variation of the PjBI model and the cognitive ability levels. This result implies that students with high-cognitive levels performed better on creative thinking skills when learning with independent PjBI, while low-cognitive students showed better creative thinking skills when learning with guided PjBI.